Implementation of Solar Panels as an Alternative to Electric Power Used in WiFi-based Freezer Box Temperature Monitoring System (Case Study of NN Frozen Food Wajak) - Mochammad Junus; Karin Febri Absari; Hudiono Hudiono; Waluyo Waluyo (Westscience Press, 2024)
A freezer box temperature monitoring system using solar panels as alternative power is an important technology to ensure the quality of stored products. This research develops a WiFi-based temperature monitoring system that uses a DS18B20 temperature sensor, a PZEM-004T digital sensor, and an ESP8266 module to read and send real-time data to a website platform. Data is collected through a temperature sensor connected to the ESP8266 microcontroller, then displayed on the LCD screen and uploaded to the server for further monitoring via WiFi connection. The results show that this system successfully maintains the freezer box temperature at optimal conditions with an average temperature value of -24.82°C and a temperature range ranging from -28.81°C to -19.63°C. The voltage values are in the range of 197.10 V - 218.70 V, current between 0.02 A - 1.03 A, and power between 158 W - 186.80 W.